A Decade of Global Navigation Satellite System/Acoustic Measurements of Back-Arc Spreading in the Southwestern Okinawa Trough - Chen, Horng-Yue; Ikuta, Ryoya; Hsu, Ya-Ju; Tsujii, Toshiaki; Ando, Masataka; Tu, Yoko; Kohmi, Takeru; Takemoto, Kiyomichi; Mizuno, Koto; Tung, Hsin; Ku, Chin-Shang; Lin, Cheng-Horng (Frontiers in Earth Science, 2021)
Long-term seafloor geodetic measurements are important for constraining submarine crustal deformation near plate boundaries. Here we present an integrated analysis of a decade of GNSS/acoustic data collected at a site 60 km to the east of northeast Taiwan near the axis of the Okinawa Trough back-arc basin. We obtained a time-series of horizontal and vertical positions based on 18 measurements from 2009 to 2019. These data reveal a southeastward movement at a rate of 43 ± 5 mm/yr since 2012 with respect to the Yangtze Plate. The horizontal motion can be explained by the clockwise rotation of the Yonaguni Block and northern Central Range. In addition, the vertical displacement of the transponder array shows rapid subsidence of 22 ± 9 mm/yr from 2012 to 2019. The fast subsidence rate and negative free-air gravity anomaly in this region indicate that crustal thinning is compensated mainly by surface deformation rather than upward migration of the Moho. Taking into account the offset in 2012 owing to the replacement of the transponder array, the horizontal position time series of our site are best explained by two linear lines with a slope change in July 2013. The timing of the velocity change coincides broadly with a change in the nearby seismicity rate and dike intrusion 150 km away from the site. Our results highlight the potential of seafloor geodesy in assessing temporal changes in deformation near the spreading center of the Okinawa Trough, which cannot be one using data from onland GNSS stations.